First known case of successful pressure ulcer treatment in a lung transplant patient with post-COVID-19 pneumonia. (2nd August 2021) - Tong, Yilan; Yu, Sijiong; Guo, Kaijun; Wang, Xiangsheng; Wu, Yang; Xia, Zhongyuan; Li, Guang; Hu, Haifeng; Yu, Mosheng; Zhu, Zhanyong
Abstract : Given the current COVID-19 crisis, multiple clinical manifestations and related complications of COVID-19 disease, especially in lung transplant patients following post-COVID-19 pneumonia, are a major challenge. Herein, we report the therapeutic course of the first reported case of sacrococcyx pressure ulcers (PU) in a 65-year-old male COVID-19 patient who underwent lung transplantation and developed a PU following surgery. We used a combination of regulated negative pressure-assisted wound therapy system (RNPT, six treatment courses, five days per treatment course), a skin tension-relief system (an intraoperative aid in minimising wounds caused by sacrococcygeal PUs) and a gluteus maximus myocutaneous flap to repair sacrococcygeal wounds. This successfully treated case provides a reference point for the treatment of similar cases.